(untitled) (Vietnam Journal of Community Medicine, 2022)
Background and Aims: Several studies have shown an association between age and BMI with semen quality, but results have been inconsistent. In Vietnam, there is no research on this issue. We carried out this study to investigate the relationship between age and BMI with the semen quality of Vietnamese men. Methods: The cross-sectional descriptive study includes 1144 semen samples collected over five years, from January 2017 to December 2021. Results: The 46-60-year-old group had significantly lower semen volume, total sperm count, and normal sperm ratio than the 16-30 and 31-45-year-old groups. The high BMI group was associated with lower semen volume and total sperm count than the other groups. The relationship between the low BMI group and semen parameters is not clear. Conclusion: Aging decreased semen volume, total sperm count, and normal sperm ratio in patients. High BMI decreased semen volume and total sperm count but reduced progressive motility in patients.